(untitled) (Global Journal of Human-Social Science, 2013)
This paper discusses how imagination mediates children s understanding of new knowledge Through a theoretical framework based on Vygotsky s concept of creative imagination this study looks at children s imagination as a way to make new information meaningful Verbal stimuli a story about the world read by four Kindergarten teachers provide grounds to investigate how children s imagination gives meaning to new information The paper reports the findings of a research project that compares and analyses the use of reading groupwork in four kindergarten schools two in Burgos Spain and two in Tampico M xico We begin by providing the theoretical stance that supports the study Next we explain the methodology used in the study The data is then discussed and interpreted While Imagination appears to be a source of information it seems to be a process generated between the teacher and the student stemming from teacher s requests